Chaperonin containing TCP1 subunit 6A may activate Notch and Wnt pathways to facilitate the malignant behaviors and cancer stemness in oral squamous cell carcinoma - Yangyi Chen; Yongge Chen; Weixian Liu (Cancer Biology & Therapy)
Chaperonin containing TCP1 subunit 6A (CCT6A) was recently discovered to be involved in cancer pathogenesis and stemness; however, its role in oral squamous cell carcinoma (OSCC) has not been reported. The current study aimed to investigate the impact of CCT6A on OSCC cell malignant behaviors and stemness and to explore its potentially interreacted pathways. SCC-15 and HSC-3 cells were transfected with the plasmid loading control overexpression, CCT6A overexpression, control knockout, or CCT6A knockout. Wnt4 overexpression or Notch1 overexpression plasmids were transfected into CCT6A-knockout SCC-15 cells. Cell proliferation, apoptosis, invasion, stemness, Notch, and Wnt pathways were detected in both cell lines, whereas RNA sequencing was only performed in SCC-15 cells. CCT6A was upregulated in five OSCC cell lines, including SCC-15, HSC-3, SAT, SCC-9, and KON, compared to that in the control cell line. In SCC-15 and HSC-3 cells, CCT6A overexpression increased cell proliferation, invasion, sphere formation, CD133, and Sox2 expression, but decreased cell apoptosis; on the contrary, CCT6A knockout exhibited an opposite effect on the above indexes. RNA-sequencing data revealed that the Wnt and Notch pathways were involved in the CCT6A’effect on SCC-15 cell functions. CCT6A positively regulates the Wnt and Notch pathways in SCC-15 and HSC-3 cells. Importantly, it was shown that activation of the Wnt or Notch pathways attenuated the effect of CCT6A knockout on SCC-15 cell survival, invasion, and stemness. CCT6A may promote OSCC malignant behavior and stemness by activating the Wnt and Notch pathways.